Enhancing Nepal’s SDG Framework: The Development of Robust Indicators for Labour Migration Monitoring - Bhatt, Anita; Bhattarai, Madhusudan (The Journal of Economic Concerns, 2025)
Labour migration and remittance inflows are very pivotal component of Nepal’s development trajectory, contributing to over 25 percent of its GDP in recent years. This has contributed significantly to household welfare, increasing local, regional and national demands for goods and services, and maintaining national macroeconomic stability. Despite its important contribution, Nepal’s Sustainable Development Goal (SDG) reporting framework has not yet fully captured the complexity of labour migration, particularly with regard to migrant workers’ rights, decent work conditions, recruitment processes, and remittance costs. This paper aims to enhance Nepal’s SDG framework by critically reviewing existing labour migration monitoring practices, examining selected regional and international experiences, and proposing a refined set of robust and contextually relevant migration-related indicators. The analysis focuses on four key SDG indicators such as 8.8.1, 8.8.2, 10.7.1, and 10.c.1covering occupational injuries, labour rights compliance, recruitment costs, and remittance costs. Drawing on a study conducted with technical support from the International Labour Organization (ILO) and in collaboration with the Central Bureau of Statistics (CBS) and the National Planning Commission (NPC), the paper assesses data sources, measurement approaches, reporting intervals, and institutional responsibilities associated with each indicator. The findings reveal substantial variation in how these indicators are defined, measured, and reported, both across countries and within Nepal. The study identifies feasible reporting intervals, appropriate data sources, and pragmatic monitoring arrangements tailored to Nepal’s institutional capacity. The paper concludes with actionable recommendations to refine indicator specifications, strengthen coordination among responsible institutions, and improve data systems for SDG reporting. By strengthening its labour migration monitoring.